Comparative efficacy of Sorafenib, and Lenvatinib in Hepatocellular Carcinoma: a meta-analysis - Monayem, Kazi Fahim (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.